A Comparison of Learning Achievement on Enjoyable Thinking with Pyramid Cone and Sphere and Problem Solving Ability of Grade 9 Students between Using MEAs and SSCS Model - Kruelamai, Papassara; Keeratichamroen, Wasana (Ratchaphruek Journal, 2024)
The purpose of this study were to compare learning achievement, problem solving ability, and learning satisfaction after learning between using of MEAs and SSCS model. The sample group of this study were 92 students of grade 9 selected by using a cluster random sampling. The research instruments were lesson plans of MEAs and SSCS model, an achievement test, a problem solving ability test, and learning satisfaction questionnaires. The data were statistically analyzed by percentage, mean, standard deviation and t-test. The findings of this research were as followed: 1) Learning achievement after learning MEAs and SSCS model was significantly higher than those before learning at .05 level. 2) Learning achievement after learning MEAs was significantly higher than after learning SSCS model at .05 level. 3) Learning achievement after learning MEAs and SSCS model was significantly higher than 70 percent criterion at .05 level. 4) Problem solving ability after learning MEAs and SSCS model was significantly higher than those before learning at .05 level. 5) Problem solving ability after learning MEAs was not significantly higher than after learning SSCS model at .05 level. And 6) Learning satisfaction after learning MEAs was significantly higher than after learning SSCS model at .05 level.